(a-b)^5÷(b-a)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:51:50
(a-b)^5÷(b-a)^2(a-b)^5÷(b-a)^2(a-b)^5÷(b-a)^2(a-b)^5÷(b-a)^2=(a-b)^5÷(a-b)²=(a-b)³(a-b)
(a-b)^5÷(b-a)^2
(a-b)^5÷(b-a)^2
(a-b)^5÷(b-a)^2
(a-b)^5÷(b-a)^2
=(a-b)^5÷(a-b)²
=(a-b)³
(a-b)³
等于(a-b)∧3
(a-b)^5÷(b-a)^2
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
化简:{[(2a-b)/(a+b)]-[b/(a-b)]}÷[(a-2b)/(a+b)]
化简(2a-b/a+b-b/a-b)÷a-2a/a-b
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
计算(a-b)^m(a-b)[2(b-a)]^3[(b-a)^5]^2÷(a-b)^m=
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
[(a+2b)(a-2b)-(2a-b)²+(3a-b)(3a-5b)]÷2a其中 a=-1,b=2
[(-a-3b)(-a+3b)-(-3b+a)^2]÷(-6/5a)
计算(5a-3b)^2+(a+b)(a-b)
2a+b/3a+5b 求a/b
(a-b)^n(b-a)^2n(a-b)^5
-2a(a+b)+b(a+b)
5(2a+b)^4÷(2A+b)^2 (a-b)(a^2+b^2)(a^4+b^4)(a+b)要有计算过程
(a-b/a+b)^3÷(a-b)^2/a+b乘(-a+b/a-b)^2
[(a²+b²)/(a²-b²)-(a-b)/(a+b)]÷2ab/[(a-b)(a+b)³]